The Effect of Liquidity, Leverage, and Profitability on Stock Prices - Adelia, Zelin Putri; Susilowati, Dwi; Moorcy, Nadi Hernadi (Riwayat: Educational Journal of History and Humanities, 2025)
The purpose of this study was to determine the variables of Current Ratio, Debt to Equity Ratio, and Return on Asset Ratio both simultaneously and partially on the Stock Price. The data used are existing sources of both internal and external data and data can be accessed via the internet and information publication. The data used is the financial statements of pharmaceutical companies listed on the Indonesia Stock Exchange for the 2019-2024 period. This study uses a quantitative approach and for analysis tools using SPSS version 25. The data analysis method uses multiple regression analysis, classical assumption test, anova test and hypothesis testing. The results showed that the Currenr Ratio variable, and Debt to Equity Ratio simultaneously had no positive and insignificant effect on Stock Price, and Return On Asset had a negative and significant effect on Stock Price.